A Review of Suicide Risk Assessment Tools and Their Measured Psychometric Properties in Korea - Baek, In-Chul; Jo, Soobin; Kim, Eun Ji; Lee, Ga Ryoung; Lee, Dong Hun; Jeon, Hong Jin (Frontiers in Psychiatry, 2021)
While there has been a slew of review studies on suicide measurement tools until now, there were no reviews focusing on suicide assessment tools available in Korea. This review aimed to examine the psychometric properties of tools developed in Korea or the translated versions from the original tools in their foreign language and to identify potential improvements and supplements for these tools. A literature search was done using the Korean academic information search service, Research Information Service System, to identify the suicide measures to be included in this review. Abstracts were screened to identify which measures were used to assess suicide-related factors. Based on the established inclusion and exclusion criteria, 18 tools remained and we assessed their psychometric properties. The current review indicated several major findings. First, many of the tools did not report predictive validity and even those with predictive validity were based on past suicide attempts. Second, some of the tools overlooked the interactive component for the cause of suicide. In addition, information to supplement the self-reported and clinician-administered reports by collecting reports from the subjects’ families and acquaintances is needed. It is also important to develop a screening tool that examines other aspects of an individual’s personal life, including unemployment, bereavement, divorce, and childhood trauma. Moreover, tools that have been studied in more diverse groups of the population are needed to increase external validity. Finally, the linguistic translation of the tools into Korean needs to consider other cultural, social, and psychological factors of the sample of interest.